Tracked Changes. Fine-cut tobacco and smoking articles made from it. Methods of sampling, conditioning and analysis. Determination of total particulate matter of smoking articles using a routine analytical smoking machine, preparation for the determination of water and nicotine, and calculation of nicotine-free dry particulate matter Part 3, (10th March 2023) - British Standards Institution,
No abstract available